First-principles investigation on the novel half-Heusler VXTe (X=Cr, Mn, Fe, and Co) alloys for spintronic and thermoelectric applications. (1st March 2023) - Sattar, Muhammad Atif; Javed, Mehreen; Al Bouzieh, Najwa; Benkraouda, Maamar; Amrane, Noureddine
Abstract: Half-Heusler (HH) alloys are a well-known and extensively researched family of thermoelectric (TE), magnetic, and spintronic materials. Doping may significantly increase the thermoelectric conversion efficiency of these materials; nevertheless, practical applications remain far. As a result, the hunt for superior parent TE alloys is critical. Using extensive first-principles density functional calculations, we predicted a novel class of vanadium-based four HH VXTe alloys, where X is one of the four elements: Cr, Mn, Fe, and Co. Their TE properties, as well as their mechanical, magnetic, electrical, and structural stability, have been studied in depth. Their mechanical and thermodynamic stability is confirmed using the predicted elastic constants, formation and cohesive energies, and phonon spectra. A comprehensive analysis of elastic constants and moduli demonstrates that HH VXTe alloys possess elastic anisotropy with reasonably good machinability, higher melting and Debye temperatures, mixed bonding characteristics with ionic and covalent contributions, and brittle nature, except for VCoTe, which is ductile. We find that the ground state of HH VCrTe and VFeTe is ferrimagnetic, while HH VCoTe is ferromagnetic and HH VMnTe is non-magnetic. Three VXTe (X = Cr, Fe, & Co) alloys demonstrated half-metallicity with 100% spin-polarization, whereas HH VMnTe is an 18-electron indirect semiconductor. In the studied HH VXTe alloys, most of the heat flow is caused by the phonon-group velocity of the acoustic phonons. Further studies on the relationship between carrier concentration and temperature dependence of TE properties reveal that the high ZT ∼1.2 at 1000 K of the pristine HH VMnTe alloy is obtained due to its high-power factor of 249.4 × 10 12 W m − 1 K − 2 and this value is greater than the values of some known pristine and doped HH TE materials. Our findings pave the way for further investigation into the HH VXTe alloys in the quest for improved TE and spintronic materials for use in domains that necessitate high thermoelectricity and spintronic performance.